Case Report: Primary cutaneous apocrine carcinoma mimicking breast carcinoma - a rare diagnostic challenge - Kameh Khosh, Masih; Hirsch, Tobias; Schulze, Hans-Joachim; Kuhnen, Cornelius; Wellenbrock, Sascha (Frontiers in Oncology, 2026)
BackgroundA 60-year-old male patient presented to a senological clinic with a left axillary tumor. The histomorphological characteristics were ambiguous, initially pointing to apocrine carcinoma of mammary origin. This suspicion led to a delay in establishing the correct diagnosis. Only after complete tumor excision and comprehensive work-up in a multidisciplinary dermato-oncological clinic could a definitive diagnosis of primary cutaneous apocrine carcinoma (PCAC) be reached, allowing for appropriate therapy to be commenced.Case PresentationThe patient had an unremarkable medical history and had presented for excisional biopsy of an axillary nodule. Following the cancer diagnosis, several diagnostic tests and histopathological evaluations were initially performed in a senological setting to assess the likelihood of (metastatic) mammary carcinoma. Workup included breast ultrasonography, CT and MRI imaging and bone scintigraphy. A previously unrecognized subcutaneous tumor mass was identified in the left axilla, located deep to the excised nodule. No further lesions, either mammary or otherwise, were detected. The patient was referred to a dermato-oncological clinic, and the subcutaneous mass, containing metastatic lymph nodes, was completely excised with clear margins. Following extensive histopathological analysis, imaging and deliberation in the interdisciplinary tumor board, mammary carcinoma and metastatic disease were ruled out and the diagnosis of primary cutaneous apocrine carcinoma was reached. Adjuvant locoregional radiotherapy could subsequently proceed.ConclusionThis case underscores the importance of an interdisciplinary approach in diagnosing axillary neoplasms and illustrates the valuable role of a high-volume, multidisciplinary skin cancer center in optimizing patient management. Although patients may initially present to a senological clinic, maintaining a broad differential diagnosis is crucial, especially when treating tumors with overlapping or atypical features. This prevents misdiagnoses, ensuring timely and effective care, thereby improving patient outcomes.